Creating Family Resilience in Indonesia: A Study of “Marriage Guidance” Program in Aceh and South Sumatera - Mursyid Djawas; Hedhri Nadhiran; Sri Astuti A. Samad; Zahrul Mubarrak; Muhammad Abrar Azizi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2022)
Indonesia still experiences the increasing of divorce rates. To address this issue, the government through the Ministry of Religious Affairs has carried out several strategic programs, including Bimbingan Perkawinan (Marriage Guidance). The study of this paper examines the influence of the program on family resilience in the provinces of Aceh and South Sumatra. It used the normative approach in sociological studies. Data were collected by means of interviews, document studies, and questionnaires. The results of the study by referring to the questionnaire and interview show that the program in Aceh and South Sumatra has been running well. However, it has not been able to create family resilience and the divorce rate still keeps increasing. It is expected that post-marriage counseling should also be conducted so that married couples can establish family resilience as aspired within the community and country.